A longitudinal study of prevalence and predictors of incidence and persistence of sub-diagnostic social anxiety among Swedish adolescents. Issue 3 (3rd July 2022) - Mörtberg, Ewa; Jansson Fröjmark, Markus; Van Zalk, Nejra; Tillfors, Maria
Abstract: This longitudinal study aimed to examine the 1-year prevalence, incidence and persistence of sub-diagnostic social anxiety (SSA) as well as general risk factors for the incidence and persistence of SSA during early and mid-adolescence. A Swedish sample of adolescents ( N = 2, 523) aged 13–14 years at Time 1 and 14–15 years at Time 2 completed measures of anxiety, depressive symptoms, stressors and emotion regulation strategies across the two timepoints. SSA was defined and assessed by the Social Phobia Screening Questionnaire for Children. The prevalence of SSA was 16%, the incidence 12%, and the persistence 53% over time. Symptoms of depression and general anxiety, various stressors and emotion regulation strategies were overall significantly related to SSA. Predictors for the incidence of SSA were lower age, female gender and elevated general anxiety and behavioral avoidance (i.e. being afraid of new activities when there is uncertainty about the outcome). Predictors for persistent SSA were female gender and increased behavioral avoidance. In conclusion, SSA is very common among young individuals, and behavioral avoidance appears particularly important for understanding the development and persistence of SSA in adolescence.